Meiotic initiation in chicken germ cells is regulated by Cyp26b1 and mesonephros. Issue 7 (3rd October 2019) - Yousefi Taemeh, Sara; Mahdavi Shahri, Naser; Lari, Roya; Bahrami, Ahmad Reza; Dehghani, Hesam
Abstract: Our knowledge of mechanisms involved in the meiosis of chicken germ cells is very limited. In mammalian fetal ovaries, the onset of meiosis is dependent on retinoic acid and subsequent upregulation of the Stra8 gene. To clarify the mechanism of meiotic initiation in chicken germ cells, we investigated the role of Cyp26b1, a retinoic acid‐degrading enzyme. The Cyp26b1‐inhibitor, ketoconazole was used to treat the ex vivo‐cultured stage 36 gonads/mesonephroi. Then, the progression of meiosis was studied by histological and immunohistochemical analysis and the level of the transcript for Stra8 was evaluated by a quantitative reverse transcription‐polymerase chain reaction in individual ketoconazole‐treated gonads after 6 days in culture. The results revealed that meiosis was induced in both testes and right ovary upon inhibition of Cyp26b1 in the ex vivo‐cultured gonads, despite downregulation of Stra8 messenger RNA in the treated gonads. Also, meiosis was observed only when mesonephros was cultured alongside the left ovary. These findings demonstrate that in chicken, Stra8 is not the only factor for the entrance into meiosis, and Cyp26b1 and mesonephros play critical regulatory roles for the sex‐specific timing of meiotic initiation in birds. Abstract : Ketoconazole inhibition of Cyp26b1 in non‐meiotic gonads allows Stra8‐independent initiation of meiosis, only in the presence of mesonephros. The meiosis initiation occurs in the left ovarian cortex (where Cyp26b1 is absent) of ex vivo‐cultured female embryos (ZW), only when the mesonephros remains attached. This suggests that a factor or factors other than retinoic acid (the inducer of Stra8), are able to travel from the mesonephros to the ovary to induce meiosis. Ketoconazole inhibition of Cyp26b1, despite the reduction of Stra8 expression, led to the meiotic initiation (only in the presence of mesonephros) in non‐meiotic gonads (i.e., the two testes and the right ovary). HIGHLIGHTS: Cyp26b1 inhibition initiates meiosis in the ex vivo‐cultured embryonic non‐meiotic gonads Initiation of meiosis in Cyp26b1‐inhibited gonads is not associated with Stra8 upregulation The presence of mesonephros is critical for meiosis initiation